Review on advances in toxic pollutants remediation by solid waste composting and vermicomposting - S. Poornima; M. Dadi; S. Subash; S. Manikandan; V. Karthik; S.R. Deena; R. Balachandar; S.K.N. Kumaran; R. Subbaiya (Scientific African, 2024)
Organic solid waste loading emerges as a serious environmental threat. Vermicomposting and composting are the two biological processes having the potential to effectively treat organic waste. In composting, in a controlled environment, microorganisms are used to treat organic wastes. Vermicomposting is a low-cost waste management technique incorporates earthworms and microorganisms to produce highly nutritive vermicompost, which in turn preserves the ecosystem. In vermicomposting, earthworms are the important players, the rate of mineralization is increased and nutritive cast is produced as a byproduct. Vermicompost improves soil aeration, microbial population, soil enzyme activity, and texture while also fostering plant growth. Crop growth and yield are greatly impacted by vermicompost. Vermicast ensures sustainable agricultural practices in addition to improve soil health and plant growth. Adsorption, precipitation, redox reactions, and complexation all work together to make heavy metals unavailable during composting. Heavy metals like mercury, cadmium, lead, copper, zinc, and manganese are bioaccumulated by earthworms. When persistent organic pollutants are composted, microbes take them up and reduce their bioavailability. Through vermicast, earthworms convert microplastics into nanoplastics. This review discusses developments in composting and vermicomposting of organic wastes, the potential contribution of earthworms, presence of heavy metals in organic waste, the influence of biochar on composting and removal of toxic pollutants through composting and vermicomposting.